2019
DOI: 10.1002/pen.25155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interfacial chemistry on crystallization of polypropylene/multiwall carbon nanotube nanocomposites

Abstract: This study systematically investigates the polymer–carbon nanotube (CNT) interaction when the interphase is tailored. Maleic anhydride‐grafted‐polypropylene (MA‐g‐PP) or polypropylene (PP) was noncovalently coated onto acid functionalized multiwall nanotube (f‐MWNT) through solution mixing. These coated f‐MWNTs were melt microcompounded with neat PP to form PP/f‐MWNT nanocomposites. The effects of functional groups and the thin layer of solution processed polymers, namely, MA‐g‐PP or PP, at the PP/f‐MWNT inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Under quiescent crystallization (no applied preshear), the crystallization rate was the fastest in p‐MWNT (5.3 min), followed by PP/f‐MWNT master batch (8 min) and MA‐ g ‐PP/f‐MWNT masterbatch (30 min)‐based nanocomposites (1 wt% MWNT), and then followed by neat PP (69 min). At 1 wt% MWNT, p‐MWNT was found to be a more effective nucleation agent then f‐MWNT due to the presence of the functional group in the latter . However, under the effect of preshear applied at 180°C, both masterbatch‐based samples exhibited a noticeable change of crystallization time while there was nearly no change in the case of neat PP and PP/p‐MWNT (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Under quiescent crystallization (no applied preshear), the crystallization rate was the fastest in p‐MWNT (5.3 min), followed by PP/f‐MWNT master batch (8 min) and MA‐ g ‐PP/f‐MWNT masterbatch (30 min)‐based nanocomposites (1 wt% MWNT), and then followed by neat PP (69 min). At 1 wt% MWNT, p‐MWNT was found to be a more effective nucleation agent then f‐MWNT due to the presence of the functional group in the latter . However, under the effect of preshear applied at 180°C, both masterbatch‐based samples exhibited a noticeable change of crystallization time while there was nearly no change in the case of neat PP and PP/p‐MWNT (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The resulting PP/f‐MWNT, MA‐ g ‐PP/f‐MWNT masterbatches or untreated pristine MWNT (p‐MWNT) were melt microcompounded with PP. In our previous works , it has been demonstrated that the noncovalently modified MWNTs by PP brought about significant improvement not only in f‐MWNT dispersion in PP but also in impact strength (152% increase in impact strength at 1 wt% CNT loading) and crystal perfection (as demonstrated by 7°C increase in peak melting temperature at 0.3 wt% MWNT loading). In this article, we study the role of noncovalently coated polymer on the rheological properties of PP/f‐MWNT nanocomposite melts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these MWNTs, an average number of 9 to 10 walls and an average diameter of 12 ± 3 nm were determined by X-ray diffraction and SEM, respectively, in previous study. [35,36] Dimethylformamide (DMF) was obtained from Sigma Aldrich (HPLC grade, >99.9% purity). Methanol (ACS grade) and glycerol were purchased from VWR Chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…[ 8–10 ] In this context, MWCNTs have shown to increase the bulk crystallization temperature ( T c ) of PP indicating the hetero‐nucleating action of MWCNTs. [ 10–13 ] However, the extent of hetero‐nucleating action of MWCNTs depends on the type of MWCNTs and dispersion state of MWCNTs in PP/MWCNTs composites. Further, dispersion of MWCNTs in PP matrix primarily depends on the extent of “agglomeration” associated with the MWCNTs type, interfacial interaction between PP and MWCNTs and the parameters used in processing.…”
Section: Introductionmentioning
confidence: 99%